ANALISA KINERJA SIMPANG TAK BERSINYAL JALAN SIMPANG BRANGGAHAN NGADILUWIH KABUPATEN KEDIRI - Aditiya Yayang Nurkafi; Yosef Cahyo; Sigit Winarto; Agata Iwan Candra (Faculty of Engineering, Kadiri University, 2019)
The development of transportation in the Kediri Regency has an impact on increasing people's daily activities in the transportation sector. So far, the Branggahan Ngadiluwih road section at the crossroads leading to the connecting bridge between Ngadiluwih sub-district and Mojo sub-district, at certain hours, there is often traffic activity due to road performance, which plays an important role in transportation activities. This study aims to determine: the value of capacity (C), degree of saturation (DS), the queue of opportunity (QP), and the value of traffic delay (DT) at the intersection. The method used is data collection based on the MKJI 1997. Based on the results of research and discussion of the performance of the Branggahan Ngadiluwih intersection, the value of the queuing opportunity is between 52.287% - 105.135%, the average value of the delay in traffic exceeds 15 sec / SMP, the value of degrees saturation exceeds the standard, namely 1.136. To reduce the delay that occurs at the intersection. That exceeds the maximum value (> 15 sec / SMP), it is necessary to install a parking restriction and stop at an approach where there is no shoulder for parking, and a traffic light is needed.Perkembangan transportasi dikabupaten kediri berdampak pada meningkatnya aktivitas keseharian masyarakat di bidang transportasi. Sejauh ini pada ruas jalan branggahan ngadiluwih di simpang jalan menuju jembatan penghubung antara kecamatan ngadiluwih dengan kecamatan mojo pada jam tertentu sering terjadi kesibukan lalu lintas karena kinerja jalan yang menjadi peranan penting dalam kegiatan transportasi. Penelitian ini bertujuan mengetahui: nilai kapasitas (C), derajat kejenuhan (DS), antrian peluang (QP) serta nilai tundaan lalu lintas (DT) pada persimpangan tersebut. Metode yang digunakan adalah pengumpulan data yang berpedoman pada MKJI 1997. Berdasarkan hasil penelitian dan pembahasan kinerja simpang Branggahan Ngadiluwih memiliki nilai peluang antrian disimpang tersebut antara 52,287% - 105,135%, nilai tundaan pada lalu lintas rata-rata melebihi 15 det/smp, nilai derajat kejenuhan melebihi standart yaitu 1,136. Untuk menurunkan tundaan pada simpang yang melebihi nilai maksimum (>15 det/smp) besarnya perlu dipasang larangan parkir dan berhenti di pendekat yang tidak tersedia bahu untuk parkir serta perlu pemasangan lampu lalu lintas (Traffic Light).